2018
DOI: 10.3389/fimmu.2018.01797
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor Nur77 Deficiency Alters Dendritic Cell Function

Abstract: Dendritic cells (DCs) are the professional antigen-presenting cells of the immune system. Proper function of DCs is crucial to elicit an effective immune response against pathogens and to induce antitumor immunity. Different members of the nuclear receptor (NR) family of transcription factors have been reported to affect proper function of immune cells. Nur77 is a member of the NR4A subfamily of orphan NRs that is expressed and has a function within the immune system. We now show that Nur77 is expressed in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 104 publications
2
36
0
Order By: Relevance
“…PDGF and hypoxia induce Nr4a3 in VSMCs [35,36]. Nr4a3 promotes proliferation by inducing Cyclin D1, Cyclin D2 and PCNA, which effect was lost with siNr4a3 treatments [35,36,37]. While Nr4a1 and Nr4a2 are protective against hypertrophy and excess muscle tissue growth, Nr4a3 promotes proliferation.…”
Section: Proliferationmentioning
confidence: 99%
“…PDGF and hypoxia induce Nr4a3 in VSMCs [35,36]. Nr4a3 promotes proliferation by inducing Cyclin D1, Cyclin D2 and PCNA, which effect was lost with siNr4a3 treatments [35,36,37]. While Nr4a1 and Nr4a2 are protective against hypertrophy and excess muscle tissue growth, Nr4a3 promotes proliferation.…”
Section: Proliferationmentioning
confidence: 99%
“…Therefore, we used an alternative approach. It has been reported that 6-mercaptopurine (6-MP) induces the expression of NR4A1 in cells [18]. Therefore, we used 6-MP to enhance the expression of Nr4a1 in SMRT depleted cDC1 to see if it can complement the IL-10 expression.…”
Section: Resultsmentioning
confidence: 97%
“…NR4A1 has been reported to positively regulate mTOR activity and thereby STAT3 phosphorylation and IL-10 expression [46]. It is also shown that deficiency of NR4A1, a member of the nuclear receptor superfamily, leads to enhanced production of IL-6, TNF-α, and IL-12 in both human and murine dendritic cells [18]. Similarly, peroxisome proliferator-activated receptor (PPAR-α) also exerts anti-inflammatory effects on monocytes and macrophages [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, studies of mouse Ly6C low monocytes, which are considered to be the murine analogs of human non-classic monocytes, whereas Ly6C hi correspond to classic monocytes, demonstrated that the transition from Ly6C hi to Ly6C low monocytes depends on NR4A1 expression [ 143 ], which is necessary for the generation and survival of Ly6C low monocytes, which are being reduced by 90% in NR4A1-deficient mice [ 144 ]. Also, it has been shown that increased NR4A1 expression levels lead to diminished MoDC and T-cell activation [ 145 ]. Furthermore, recent studies with NR4A3-deficient mice show that NR4A3 expression is required to skew monocyte differentiation toward MoDCs and allows the acquisition of migratory characteristics required for MoDC function [ 146 ].…”
Section: Immunoregulatory Populations In the Context Of Natural Immentioning
confidence: 99%